A Comparative Study of the Removal of Heavy Metal Ions from Synthetic Wastewaters Using Different Adsorbents - Emmanuel A. Oluyemi; John A.O. Oyekunle; Samuel O. Olasoji (Adsorption Science & Technology)
A comparison has been made of the efficiency of heavy metal ion adsorption from synthetic wastewaters by charcoal prepared locally from the burnt remnants of plantain peel with more conventional adsorbents such as industrial activated wood charcoal, technical charcoal animal powder and Amberlite resin. Thus, mixed standard solutions (100 mg/ℓ) of copper and lead ions adjusted by buffer solutions to pH values of 5, 7 and 9, respectively, were allowed to flow through adsorbent columns which were 10, 20, 30, 40 and 50 cm in length. The concentrations of the heavy metal ions in the mixed standard solutions were determined before and after contact with the adsorbents via atomic absorption spectrophotometry (AAS). The adsorption capacities of the various adsorbents based on the overall percentage removal of Cu 2+ ions at pH 9 employing a column of 50 cm length were in the order: Amberlite resin (98.89 ± 7.59%) > plantain peel charcoal (98.56 ± 6.72%) > technical charcoal animal powder (96.87 ± 5.78%) > activated wood charcoal (93.64 ± 7.29%). The corresponding order for Pb 2+ ions at a pH value of 7 employing a column of 50 cm length was: Amberlite resin (99.98 ± 7.53%) > plantain peel charcoal (98.37 ± 7.95%) > technical charcoal animal powder (97.91 ± 6.83%) > activated wood charcoal (96.39 ± 7.06%).